2008
DOI: 10.1111/j.1872-034x.2008.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of B‐Myb by E2F1 in hepatocellular carcinoma

Abstract: MYBL2 is a probable transcriptional target of E2F1 in HCC and may therefore be a useful biomarker for diagnosis and an attractive target for molecular therapies useful to treat HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 30 publications
3
56
0
Order By: Relevance
“…In agreement with previous data obtained in other cell models (36)(37)(38), our present findings also suggested that E2F1 is involved in B-Myb downregulation at transcriptional level. First of all, we could show that the modulation of mRNA levels of E2F1 and B-Myb transcription factors, assessed in response to Nutlin-3 in all cell types investigated, significantly and positively correlated.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In agreement with previous data obtained in other cell models (36)(37)(38), our present findings also suggested that E2F1 is involved in B-Myb downregulation at transcriptional level. First of all, we could show that the modulation of mRNA levels of E2F1 and B-Myb transcription factors, assessed in response to Nutlin-3 in all cell types investigated, significantly and positively correlated.…”
Section: Discussionsupporting
confidence: 83%
“…By computational analysis (as predicted by SABiosciences' Text Mining Application and the UCSC Genome Browser) both E2F1 and B-Myb promoters exhibit several p53 consensus DNA binding sites, which have previously suggested a gene regulation/repression occurring through p53 binding directly to the consensus DNA binding sequences (36,37). In addition, E2F1 DNA binding sites have been found in the B-Myb regulatory region, indicating that a potential regulation of B-Myb is also mediated by E2F1 (36)(37)(38).…”
Section: Transcriptional Downregulation Of B-myb and E2f1mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that MYBL2 overexpression in different tumours, including HCC [18, 22, 23], and MYBL2 has been implicated in the progression of breast cancer and colorectal cancer [19, 20, 24]. However, the expression and biological function of MYBL2 in GBC have not been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant B-MYB expression or amplification has been documented in different types of human cancers, suggesting a role in tumorigenesis [33][34][35]. Furthermore B-MYB was recently implicated in the maintenance of pluripotency, chromatin stability and normal cell cycle progression [36][37][38].…”
Section: Discussionmentioning
confidence: 99%